Pociągi Joanny Chmielewskiej - Gazdecka, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses the presentation of space in Joanna Chmielewska authobiography, related mainly to the subject matter of railway travel. It cites examples of human behaviour during train journeys in times of the People's Republic of Poland, relevant from the point of view of cultural studies. The paper covers the issue of space and distance presentation in relation to interpersonal relationships, the author sensitivity and the content of the author's work.
Keywords: Chmielewska, Joanna (1932-2013); autobiografia; pociągi; przestrzeń; PRL; authobiography; space; trains; People's Republic of Poland